"I'm eating healthy now": The relationship between perceived behavior change and diet. (April 2021) - Szymczak, Hermann; Keller, Lucas; Debbeler, Luka J.; Kollmann, Josianne; Lages, Nadine C.; Sproesser, Gudrun; Gollwitzer, Peter M.; Schupp, Harald T.; Renner, Britta
Highlights: A comprehensive diet shift was necessary for people to perceive a change (Changers). Changers changed from a regular to an optimal dietary pattern. Changers showed a significant decrease in their body mass index. Main findings were replicated in a second study. Abstract: Public health campaigns often encourage people to increase the consumption of vegetables and fruits while limiting sugar, fat, and salt intake. Furthermore, recent approaches increasingly suggest accumulating small behavioral shifts to change eating behavior. However, when individuals actually do notice a positive change in their diet behavior has rarely been studied to date. Accordingly, the present research examined the relationship between felt and actual changes in healthy food intake. Food choice was assessed in two longitudinal studies (Study 1: N  = 743; Study 2: N  = 489) using a validated food frequency questionnaire. For assessing perceived healthy eating shifts, participants stated at a second measurement-point whether they had changed their eating patterns in the previous six months. Accordingly, participants were classified into four 'Perceived Change' groups: Changers, Attempters, Non-Attempters, and Healthy Eaters. In Study 1, participants who claimed they had made a healthy shift in their eating behavior (Changers) shifted from a regular to an optimal dietary pattern. Furthermore, Changers reduced their intake of five food categories: chocolate, cakes/pastries/biscuits, sausages/ham, meat, and eggs. No systematic changes were observed in the remaining groups. These results were replicated in Study 2. Participants perceived a change in their diet only if they had achieved a healthy shift in their dietary pattern. Moreover, Changers in both studies exhibited a significant decrease in their BMI. Overall, the group of Changers improved their diet, potentially reducing their risk for non-communicable diseases. Implications of these findings for public health campaigns are discussed.